“So le trar”: a reading of image and belonging in female identity (Research, Society and Development, 2022)
In the woman's identity, belonging to the so-called feminine universe, both in the private and in the public sphere, is intrinsically related to factors that break paradigms and promote gender equality. Therefore, in this study, through a corpus interweaving, it is proposed to carry out an in-depth reflection on this issue. Therefore, to think about citizenship in a post-critical perspective, we use the concepts of “foreigner” and “hospitality” by Jacques Derrida. In addition, in the research, it was elementary to understand the definition of space, an emblematic conception of geographic thought and knowledge, through the post-structuralists Homi Bhabha, Joaquim Dolz and Doreen Massey. As for the interpretative field, the post-critical and post-foundationist approaches of Alice Casimiro Lopes and Elizabeth Macedo were used. It was a study with a bibliographical and documentary approach, which was carried out using the inductive method; which aimed to reflect on the image and belonging in the female identity. It is concluded that the reading of written texts and images, as well as literature, are significant tools for the construction of identity and female empowerment.